Learning English Through Instagram: The Social Media Experiences of Gen Z Students at Nurul Jadid University - Ningrum, Bila Ayu Sheptia; Pranata, Mohammad Sofyan Adi (Journal of English Language and Education, 2025)
This study aims to explore Generation Z students’ experiences in learning English through Instagram. As digital natives, Gen Z learners are familiar with visual and interactive platforms, making Instagram a potentially engaging tool for language learning. This research employed a qualitative descriptive method, involving in-depth interviews with female participants aged 19–22 years. Data were collected through interviews and documentation, then analyzed using thematic analysis involving data reduction and categorization. The findings indicate that Instagram supports English learning across various dimensions, including vocabulary acquisition, grammar comprehension, pronunciation, speaking fluency, and writing skills. Features such as reels, infographics, live sessions, and story quizzes were identified as the most impactful. Participants reported affective benefits such as increased motivation, confidence, and cultural awareness. However, they also encountered challenges, including distractions, low-quality content, and lack of structured guidance. To overcome these obstacles, students adopted strategies such as curating their feeds, saving educational content, setting language learning goals, and creating their own content. The discussion highlights how Instagram’s features align with Gen Z’s learning preferences and its potential to complement formal education. In conclusion, Instagram offers a relevant, engaging, and multimodal environment for English language development when used consciously and strategically. It is recommended that educators integrate social media into their teaching practices while promoting digital literacy and learner autonomy to maximize educational outcomes.